PERBEDAAN PEMBELAJARAN E-LEARNING PADA MASA PANDEMI (COVID-19) DENGAN HASIL BELAJAR MAHASISWA DIPLOMA III KESEHATAN GIGI DAN TERAPI GIGI JURUSAN KEPERAWATAN GIGI - Afifah, Aulia Ade (Poltekkes Kemenkes Banjarmasin, 2022)
Online learning was carried out when the COVID-19 pandemic swept across the world, resulting in face-to-face learning being carried out by distance learning. With online learning, student learning outcomes with increasingly sophisticated technological capabilities. Online learning helps the dissemination of information is carried out directly and simultaneously, and the response is positive because it provides effective time savings in disseminating information.This type of research is a quasi-experimental or quasi-experimental research with the research design used is a pre-test and post-test group. Samples taken by purposive sampling technique are 181 samples from 377 populations in the Department of Dental Nursing. The analysis was performed using the Wilcoxon test.The results of this study showed a score of 0.00 (ρ<0.05). There was a significant difference in e-learning during the pandemic (COVID-19) with the learning outcomes of Diploma III Dental Health and Dental Therapy, Department of Dental Nursing.Conclusion of this research. There are differences in e-learning learning during the pandemic (COVID-19) with the learning outcomes of Diploma III Dental Health and Dental Nursing Department students. It is hoped that the students of the Dental Nursing Department can maintain the learning outcomes carried out by e-learning or face-to-face.